STRATEGI PENGEMBANGAN AYAM SENTUL DI KABUPATEN CIAMIS - Agus Yuniawan Isyanto; Sudradjat Sudradjat; Mohamad Iskandar (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2017)
This research was conducted with the aim to formulate Sentul chicken development strategies in Ciamis. The research was conducted using the survey method. Research was conducted in September and October 2015. Respondents consisted of:  (1) Breeders chicken Sentul many as 36 people, and (2) Other respondents, namely civil servants / government agencies and academia as many as 8 people. The research data consist of primary data and secondary data. Sentul chicken development strategy in Ciamis formulated using SWOT analysis.The results showed that the chicken Sentul development strategy in Ciamis are: (1) Increasing the supply of day old chick (DOC) to meet the needs of farmers, (2) Increase the supply through the improvement of the chicken population Sentul to meet consumer demand for chicken meat, (3) Making the chicken Sentul production centers to anticipate conflict of interest about land using between chicken Sentul farming Sentul and settlement as, also easily to facilitate in monitoring the health of chickens Sentul, (4) The increase in the number of holdings chicken Sentul per farmer via credit scheme program with an emphasis on monitoring and evaluation in order to right on the goals and objectives, (5) Improved technical capacity of farmers in raising chickens Sentul through extension activities, training and technical assistance to improve productivity, (6) Increased efficiency and productivity through production policies are supported by cross-sectoral coordination is good, (7 ) Production subsidies to ensure continuity of production that is not significantly affected by fluctuations in the price of the means of production, and (8) Improved management capabilities of Sentul chicken farmers in health through counseling activities, training and technical assistance to support the achievement of efficiency and high productivity